Solid pseudopapillary tumor associated with agenesis of the dorsal pancreas: a case report - Daniel Paulino Santana; Diogo Viana Abreu; Edmilson Celso Santos; Bruno de Lima Rodrigues; Anna Carolina D’Ascenção Maia; Marcos Campos Wanderley Reis (Brazilian Journal of Oncology)
Solid pseudopapillary tumors (SPTs) of the pancreas are rare tumors with low potential for malignancy, uncertain lineage, and favorable prognosis in most cases. The SPT has an excellent prognosis, and the standard treatment is surgical resection. The agenesis of the dorsal pancreas (ADP) is an extremely rare type of congenital pancreatic malformation and is characterized by partial or total loss of the body and tail of the gland. Its association with SPT has been reported only in two studies. We report a case of SPT associated with total ADP. A 36-year-old woman was diagnosed with a complex mass on pancreatic head topography, measuring 7.8×5.5cm, associated with complete agenesis of the body and tail of the pancreas. She underwent gastropancreatoduodenectomy with a successful postoperative outcome. The anatomopathological examination suggested an SPT and it was confirmed by immunohistochemistry.